Hubungan Pengetahuan Ibu Dengan Perilaku Pencegahan Pneumonia Pada Balita Di RSUD Harapan Dan Doa Kota Bengkulu Tahun 2026 - Dayang Pertiwi; Ravika Ramlis; Meri Epriana Susanti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Globally, there are more than 1,400 cases of pneumonia per 100,000 children, or equivalent to 1 case in every 71 children per year. The highest incidence rates are recorded in South Asia (2,500 cases per 100,000 children) and West and Central Africa (1,620 cases per 100,000 children). Meanwhile, in Indonesia, based on the 2023 Indonesian Health Survey, the number of toddlers with pneumonia reached 86,364 cases. The purpose of this study was to determine the relationship between mothers' knowledge and pneumonia prevention behaviours in toddlers at the Harapan dan Doa Regional General Hospital in Bengkulu City in 2026.The research method used was descriptive research with a cross-sectional approach. The sampling technique used was purposive sampling with a sample size of 62 mothers of infants at Harapan and Doa Regional General Hospital in Bengkulu City in 2026.The results of the univariate analysis showed that most of the respondents (53.2%) had adequate knowledge and most of the respondents (66.1%) had good pneumonia prevention behaviour in infants. The results of the bivariate chi-square test analysis showed a relationship between mothers' knowledge and preventive behaviour against pneumonia in toddlers at the Harapan dan Doa Regional General Hospital in Bengkulu City in 2026 (p-value 0.000). There is a relationship between mothers' knowledge and preventive behaviour against pneumonia in toddlers at the Harapan dan Doa Regional General Hospital in Bengkulu City in 2026.The researchers recommend that hospitals use this information as additional material to improve and develop information about pneumonia.